China's Gaofen-3 Satellite System and Its Application and Prospect - Liangbo Zhao (IEEE, 2021)
The Gaofen-3 (GF-3) satellite is China's first civilian quad-polarized C-band imaging microwave satellite that can provide high-resolution marine and land observations. Also, it is China's first low Earth orbit remote sensing satellite with a design life of eight years. During the design and development of this satellite, many major challenges have been overcome, such as the design of complex radio frequency channels, difficult system integration, high quantitative requirements, and strict component life requirements. In this article, a series of independent technological innovations in the development of GF-3 is presented. Meanwhile, the on-orbit operation of the satellite in the past five years is introduced, as well as the application of satellite data in marine observation, emergency relief, disaster reduction, surveying and mapping, water conservancy, etc. The further advancement and improvements of the GF-3 satellite are described at the end of this article.